1971
DOI: 10.1063/1.1653683
|View full text |Cite
|
Sign up to set email alerts
|

X-RAY DIFFRACTION FROM PIEZOELECTRICALLY AMPLIFIED SHEAR WAVES IN THE 50-GHz RANGE

Abstract: X-ray diffraction from piezoelectrically amplified acoustic shear waves in GaAs is reported. The spectrum of amplified acoustic flux is obtained in the microscopic limit, where the electron mean free path is much greater than the acoustic wavelength. The peak acoustic intensity occurs at 50 GHz, which corresponds to the frequency of maximum net gain according to the linear theory. The spectrum of piezoelectrically amplified acoustic waves is observed at frequencies an order of magnitude larger than may be stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1974
1974
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Since the pioneering papers of Fox & Carr (1931), Langer (1931) and Barrett & Howe (1932), diffraction of X-rays and neutrons in a crystal volume modulated by ultrasonic waves has attracted a large number of experimental and theoretical studies (White, 1950;Saccocio et al, 1967;Haruta, 1967;Carlson et al, 1971;Kö hler et al, 1974;LeRoux et al, 1975LeRoux et al, , 1976Entin & Assur, 1981;Chapman et al, 1983;Punegov & Pavlov, 1994). The observed experimental rocking curves were explained using the dynamical scattering theory (Kö hler et al, 1974;Authier, 2001), including the phenomenon of X-ray acoustic resonance (Entin & Assur, 1981;Punegov & Pavlov, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Since the pioneering papers of Fox & Carr (1931), Langer (1931) and Barrett & Howe (1932), diffraction of X-rays and neutrons in a crystal volume modulated by ultrasonic waves has attracted a large number of experimental and theoretical studies (White, 1950;Saccocio et al, 1967;Haruta, 1967;Carlson et al, 1971;Kö hler et al, 1974;LeRoux et al, 1975LeRoux et al, , 1976Entin & Assur, 1981;Chapman et al, 1983;Punegov & Pavlov, 1994). The observed experimental rocking curves were explained using the dynamical scattering theory (Kö hler et al, 1974;Authier, 2001), including the phenomenon of X-ray acoustic resonance (Entin & Assur, 1981;Punegov & Pavlov, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…A preliminary evaluation [4] of corresponding experiments was based on the kinematical theory and gave too high frequencies since multi-phonon scattering was neglected. Investigations of Carlson et al [5] with acoustoelectrically vibrating GaAs a t frequencies of about 50 GHz showed increased angular resolution but considerably reduced intensity of inelastic scattering.…”
Section: Acoustoelectrical Vibration Generation [3]mentioning
confidence: 96%
“…like CdS [5] and GaAs [6] and piezo-electric insulators like quartz [7] excited in the GHz-frequency range. In these experiments only a broadening of the wings of the associated Bragg peaks was observed as a consequence of the excited ultrasound and hypersound modes.…”
Section: Introductionmentioning
confidence: 99%